Skrining Aktivitas Antibakteri Bacillus sp. PCAR1 dari Rumput Laut Eucheuma spinosum terhadap Bakteri Staphylococcus aureus - Ni Made Alit Yulianti; Anak Agung Gede Indraningrat; Ni Wayan Widhidewi (Aesculapius Medical Journal, 2024)
[Antibacterial Activity Screening of Bacillus sp. PCAR1 from Seaweed Eucheuma spinosum against Staphylococcus aureus bacteria] Microorganisms associated with marine organisms have the potential to produce secondary metabolite compounds with strong antibacterial activity. Previous research has isolated Bacillus sp. bacteria encoded as PCAR1 from Eucheuma spinosum seaweed with antibacterial potential against Gram-positive and Gram-negative bacteria. However, the potential bioactivity produced by bacillus sp. PCAR1, especially as an antibacterial against Staphylococcus aureus, still needs to be explored using chemical extraction method. In this research, a total of 100 mL of sterile NB liquid media containing the cell mass of Bacillus sp. PCAR1 was fermented for 5 days and then shaken at 150 rpm. The supernatant was separated from the cell mass by filtration using Whatman filter paper no.1.The filtrate was extracted using ethyl acetate pro-analytics (1:1 v/v). The extracts were analyzed for antibacterial activity using the Kirby-Bauer method, while the chemical composition of the extracts was analyzed using gas chromatography-mass spectrometry (GC/MS) method. Antibacterial screening of ethyl acetate extract of Bacillus sp. PCAR1 showed an inhibition zone of 6.23±0.06 mm against Staphylococcus aureus ATCC 25293, which is classified as moderate antibacterial activity. GC/MS analysis showed that the ethyl acetate extract contained 10 chemical compounds that have potential as antibacterial, with four dominant active compounds namely p-Xylene (7.26%), Ethanol, 2-butoxy (5.36%), o-Xylene (3.14%), and mesitylene (3.41%). Overall, these results provide an initial overview of antibacterial compounds that can be synthesized by Bacillus sp. PCAR1.